Application of MOKA informal knowledge models for building knowledge based engineering systems in aircraft wind tunnel test models - Lam, Diem Huynh (Cranfield University, 2004)
Knowledge based engineering (KBE) applications are softwares that rely on some well defined engineering rules, relationships and logics for performing generative engineering tasks. A generative function is a function that is responsible for performing and obtaining generative tasks and solutions based on the given rules, relationships and logics. Presently, it is considered that there is a lack of visibility, transparency, traceability and accountability when KBE applications are used. The present research programme aims to overcome this problem by developing and integrating the knowledge model with the design automation model of KBE applications. Thus, the inner working and design of the generative function with its engineering rules and relationships defined for the KBE application may be readily seen and understood by viewing the knowledge models. Consequently, this means a degree of visibility, traceability and accountability is achieved when KBE applications are used to perform generative engineering designs. The knowledge model has been developed in accordance with the European MOKA’s methodology and takes the form of an informal knowledge model (ICARE forms). The knowledge model (ICARE forms) serves the purpose of defining how products/assemblies/parts should be designed, processed and manufactured within a set of prescribed illustrations, constraints, activities, rules and entities. The CATIA (Knowledgeware) KBE application is used by the present study and the design automation model residing on the KBE application has been developed using the Knowledgeware programming language, VBScript, macros and CAA IDL API, which allow a series of modelling and design tasks to be automated. The research programme is validated by means of a case study involving an aircraft wing model supplied by industrial collaboration partners. The present study shows that KBE technology may be used to produce substantial commercial benefits in terms of time, cost and speed. The study believes that the MOKA’s methodology and ICARE forms may be used to capture knowledge for KBE applications but there is a limit on how well, easy and complete the ICARE forms can be used to depict the engineering rules and relationships that have been defined for the generative design function of KBE applications. Parts of the work presented in this study have been demonstrated to the industrial collaborators and included in a consortium confidential DTI’s research project grant report (DTI’s ref. no. CHAD/002/00008) [1] on the use of KBE systems.